Were it as if beyond an institution that is - Ayas, Defne 1976- (Witte De With Publishers, 2017)
What is hidden, forgotten, cast away, or overlooked in the day-to-day operations of a cultural institution? How does one make tangible the container of knowledge that envelops the factual succession of exhibitions and publications? Can artists become active and responsible co-creators of institutions, their politics, and representations? Artists Bik Van der Pol are invited by Witte de With Director Defne Ayas to highlight what might otherwise become lost in both the history of the institution as well as art's history in the city of Rotterdam. Paying close attention to the socio-economic and political context in which the institution was created, Bik Van der Pol's process carried out in close dialogue with artists and staff members examines and actively exposes that which lies concealed in the folds of history. Equating seemingly-in-the-fringes material-leftovers, support structures, plans, notes, stories, and witness reports' to the level of artworks, and so exploring the viability of approaching "archival document" as "art," and "art" as "source material," the artists revive histories preserved in the documentation of exhibitions, while reenergizing the work of artists such as John Ahearn, Ken Lum, Antoni Muntadas, Eugenio Dittborn, Eleanor Bond, John Knight, and Allan Sekula. The exhibition is complemented by several guest readings into the methodologies and choices of display. Exhibition: Witte de With, Rotterdam, The Netherlands (27.05.-21.08.2016)
Titeldaten vom Cover
'Bik Van der Pol - Where it as if', (27 May - 21 August 2016), Witte de With, Center for Contemporary Art
Keywords: Pol, Jos van der -- 1961-; Pol, Liesbeth van der -- 1959-; Witte de With Center for Contemporary Art; Bildband; Ausstellungskatalog -- Witte de With, Center for Contemporary Art -- 27.05.2017-21.08.2016 -- Rotterdam